2017
DOI: 10.1007/s40097-017-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on doping of polyaniline with graphene and multi-walled carbon nanotubes

Abstract: This study reported the doping of polyaniline (PANI) with graphene (G) and multi-walled carbon nanotubes (MWCNTs) by in situ polymerization. The molecular structure of PANI and its composites was observed by FTIR, which shows that the intensity of composites peaks are higher than pure PANI due to charge transfer between the PANI and graphitic allotropes. The structural information and crystallinity of PANI and its composites can be deduced from X-ray diffraction. The morphological characterization was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 48 publications
(63 reference statements)
2
32
0
Order By: Relevance
“…The patterns of all NCs generally have the same behavior as CPA. The existence of the crystalline peak at 26° with higher intensity in NCs is due to the overlapping of CPA and graphitic materials which appear at CNMs, and this will result in an enhancement of long‐range conjugation and denotes improvement of π ‐ π interchain‐stacking 60‐61 . The appearance of these peaks is ascribed to the formation of the core‐shell structure of CNMs ‐CPA, and this is compatible with SEM and TEM analysis as we will see later.…”
Section: Resultssupporting
confidence: 76%
“…The patterns of all NCs generally have the same behavior as CPA. The existence of the crystalline peak at 26° with higher intensity in NCs is due to the overlapping of CPA and graphitic materials which appear at CNMs, and this will result in an enhancement of long‐range conjugation and denotes improvement of π ‐ π interchain‐stacking 60‐61 . The appearance of these peaks is ascribed to the formation of the core‐shell structure of CNMs ‐CPA, and this is compatible with SEM and TEM analysis as we will see later.…”
Section: Resultssupporting
confidence: 76%
“…Specific features are analyzed as follows: FT-IR spectra showed that the −OH stretching mode of TERGO and N-H stretching vibration of a secondary amine in the PANI backbone completely disappeared (see the inset of the emeraldine base structure, Figure 9). An important reduction in the intensity is observed in the quinonoid stretching ring (1559 cm −1 ) and C-N + stretching on the polaron structure (1235 cm −1 ) [70][71][72][73][74]. Thus, FT-IR spectra evidence that with the amount of TERGO powders, the transmittance is gradually reduced.…”
Section: Uv-vis Spectroscopy Of Pani/tergo Compositesmentioning
confidence: 95%
“…PANI layer deposited on ZnO surface quenches some of XRD peaks, related to ZnO. New peaks at 25.88, 27.08, 28.83°were attributed to PANI peaks, related to (200), (121) and (022) PANI crystallographic planes [15]. The XRD peaks point the forming of crystalline conductive PANI in the form of emeraldine salt [15].…”
Section: Structural Properties Of Zno-pani Nanocompositesmentioning
confidence: 98%
“…New peaks at 25.88, 27.08, 28.83°were attributed to PANI peaks, related to (200), (121) and (022) PANI crystallographic planes [15]. The XRD peaks point the forming of crystalline conductive PANI in the form of emeraldine salt [15]. Peaks of ZnO at 55.88, 60.2 and 64.88 are shifted due to forming of ZnO/PANI composite structure [16].…”
Section: Structural Properties Of Zno-pani Nanocompositesmentioning
confidence: 99%